A brief history and indications for cesarean section (Journal of Patan Academy of Health Sciences, 2021)
Cesarean section (CS) is one of the oldest surgical operations. Originally, this surgery was performed post-mortem by cutting open the woman’s abdomen to remove a dead or alive fetus. It was therefore not intended for saving the mother in ancient times. Roman law and religious rituals shaped the procedure until the Middle Ages. At that time, the indication of CS was only post-mortem. Although CS became a medical procedure in the Renaissance, maternal mortality was extremely high, mainly due to hemorrhage and puerperal infection. The reason for performing CS was to rescue the mother and fetus from protracted labor as a last resort. Since the late 19th century, with the introduction of chloroform and the developments of surgical techniques, and the availability of blood transfusion in the early twentieth century, CS became a relatively safe procedure, further helped by the introduction of antibiotics after World War II. Then, CS was increasingly an intervention to preserve the health and safety of both mother and fetus. During the 21st century, CS has been performed even without medical indication, such as maternal choice. Advancement of obstetric practice technologically and professionally during the period as well as changing attitudes of both obstetricians and childbearing women meant indications for CS are no longer limited to medical/obstetric indications. CS is perceived as a safer mode of childbirth.  Therefore, the indications of CS have been changed drastically from ancient times (rescuing a baby from dying or dead mother) to the 21st century (maternal choice/reproductive rights).